Konfokale Lasermikroskopie bei Shiitake-Dermatitis - Cussigh, Christiane; Müller-Christmann, Christine; Winkler, Julia K.; Toberer, Ferdinand; Enk, Alexander (Der Hautarzt, 2019)
Shiitake dermatitis usually occurs 1-2 days after consumption of incompletely cooked or raw shiitake mushrooms and is characterized by linear, pruritic, erythematous papulovesicular rashes. It is caused by lentinan, a polysaccharide component of the cell walls of shiitake mushrooms. The histological examination showed an eczema-like morphology with spongiosis and lymphohistiocytic infiltrates. The results of reflectance confocal microscopy (RCM) correlated with the histopathological investigations. Therefore, RCM can be used for non-invasive diagnostic confirmation of Shiitake dermatitis in the future.